2016
DOI: 10.1039/c6ra01592a
|View full text |Cite
|
Sign up to set email alerts
|

Size dependence of silver nanoparticles in carboxylic acid functionalized mesoporous silica SBA-15 for catalytic reduction of 4-nitrophenol

Abstract: Silver nanoparticles with a size around 3 nm are formed within the mesopores of –COOH functionalized mesoporous silica SBA-15, and they are highly active in the catalytic reduction of 4-nitrophenol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 75 publications
3
8
1
Order By: Relevance
“…And the turnover frequency, defined as moles of 4‐NP reduced per mole of Ag per unit time, was calculated to be 2893 h −1 for the reduction of 4‐NP. This quantified activity parameters are superior to previously reported results of related template‐based metallic catalyst used in 4‐NP reduction reactions: MpSi‐Pd catalyst (TOF: 85.1 h −1 ), nano‐Au fixed on glass fibers (TOF: 324 h −1 ), Ag@FDU‐15 nanocomposites (TOF: 444 h −1 ), Pd–ZnO hybrid nanocatalyst (TOF: 518.4 h −1 ), AuNPs/AOBC nanohybrids (TOF: 1190 h −1 ), and Ag(0.3)@SBA‐15‐(10) nanocatalyst (TOF: 1210 h −1 ) . More literature and information are listed in Table S3 (Supporting Information).…”
Section: Resultscontrasting
confidence: 54%
“…And the turnover frequency, defined as moles of 4‐NP reduced per mole of Ag per unit time, was calculated to be 2893 h −1 for the reduction of 4‐NP. This quantified activity parameters are superior to previously reported results of related template‐based metallic catalyst used in 4‐NP reduction reactions: MpSi‐Pd catalyst (TOF: 85.1 h −1 ), nano‐Au fixed on glass fibers (TOF: 324 h −1 ), Ag@FDU‐15 nanocomposites (TOF: 444 h −1 ), Pd–ZnO hybrid nanocatalyst (TOF: 518.4 h −1 ), AuNPs/AOBC nanohybrids (TOF: 1190 h −1 ), and Ag(0.3)@SBA‐15‐(10) nanocatalyst (TOF: 1210 h −1 ) . More literature and information are listed in Table S3 (Supporting Information).…”
Section: Resultscontrasting
confidence: 54%
“…Moreover, the use of copper nanoparticles (CuNPs) is restricted by Cu’s inherent instability under atmospheric conditions, which makes it prone to oxidation. Some supporting materials increase the stability of CuNPs by altering their sensitivity to oxygen, water, and other chemical entities, which has encouraged the exploration of alternative Cu-based NPs with more complex structures [ 12 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Kao et al [46] reported the formation of Ag NPs inside the mesoporous silica SBA-15 functionalized with -COOH groups as the support. The acetate (-COO − ) groups effectively interacted with the Ag + ions, thus allowed for a facile fabrication of small-sized Ag NPs down to 3.0 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the catalytic activities of Ag NPs-loaded silica SBA-15 composites toward the reduction of 4-NP in the presence of NaBH 4 was investigated by Guo and coworkers [47]. The particle size of Ag plays a definitive role in determining their catalytic activity [46,47]. Furthermore, uniform sized spherical, and rod-shaped Ag NPs have been successfully deposited inside the mesochannels of SBA-15 via a simple chemical method [48].…”
Section: Introductionmentioning
confidence: 99%